The Influence of Liquidity, Leverage, Total Asset Turnover, Corporate Social Responsibility and Independent Board of Commissioners on Financial Performance in Agricultural Sector Companies Listed on the Indonesia Stock Exchange for the 2014-2019 Period - Bayu Wulandari; Jean Rainey Yuslim; Erlyn Chandra; Cherrie; Cindy (Jurnal Mantik, 2021)
The purpose is to examine and analyze how the influence of Liquidity, Leverage, Total Asset Turnover, Corporate Social Responsibility and Independent Board of Commissioners on Financial Performance. This population is agricultural sector companies totaling 21 companies. The research sample got 8 companies with purposive sampling technique. This statistical method is multiple linear. The results of the study indicate that Liquidity, Leverage, Corporate Social Responsibility and Independent Board of Commissioners have no effect on Financial Performance. While Total Asset Turnover has a significant effect on Financial Performance. And simultaneously Liquidity, Leverage, Total Asset Turnover, Corporate Social Responsibility and Independent Board of Commissioners have an effect on Financial Performance. The magnitude of the coefficient of determination is 49, 7% while the remaining 50.3% Financial Performance is explained by other variables not examined in this study. The conclusion of this study is that only Total Asset Turnover has a significant effect on financial performance in agricultural sector companies listed on the Indonesia Stock Exchange for the 2014-2019 period.